Spectacles of Reform : Theater and Activism in Nineteenth-Century America - Hughes, Amy (Book collections on Project MUSE., 2012)
Explores how and why spectacle is a crucial component of the reform apparatus and a defining characteristic of American activism in general, whether highly organized or quietly quotidian. It advocates for a consideration of spectacle as methodology : a unique system of communication, employed in myriad context, that rehearses and sustains conceptions of race, gender and class in extremely powerful ways. Spectacle capitalizes on the sensational and the profane, embracing what is deliberately hidden or secretly imagined and giving it material form.